Emotion, rationality and argumentation in judicial adjudication - Sotomayor Trelles, José Enrique (2017)
Based on the theory of the emotions proposed by Martha Nussbaum, the present paper proposes a theory of rationality and judicial reasonability that includes emotions as a necessary element. With this, it is possible to pass from a purely deliberative-abstract model of judicial argument to a narratively open one, in which empathy and literary imagination play a fundamental role. I will argue that emotions have a concrete manifestation in at least three relevant circumstances: the value of testimony, that of empathy, and that of literary imagination. However, the place of emotions for the project of judicial rationality is subject to institutional restrictions such as rules of law, procedures and precedents. With this in mind, a sketch of theory on the narrative rationality in judicial contexts is presented in the last section of this paper.